Optimisation of surface roughness with GA approach in turning 15% SiCp reinforced AlSi7Mg2 MMC material - Ozel, Cihan; Kilickap, Erol (My University, 2006)
In this study, 15% SiCP reinforced Metal Matrix Composite (MMC) AlSi7Mg2 material was turned by an uncoated WC cutting tool (K10) at cutting speeds of 50, 100 and 150 m/min, feed rates of 0.1, 0.2 and 0.3 mm/rev and depths of cut of 0.5, 1 and 1.5 and surface roughness values have been examined after each workpiece machined. A mathematical expression was derived by means of regression analysis method using the results obtained from the experiments performed under these conditions. Then, with the help of this expression, optimum turning parameters for minimum surface roughness were found via Genetic Algorithm (GA). © 2006 Inderscience Enterprises Ltd.
Keywords: Genetic Algorithm (GA); optimisation; surface roughness; turning parameters